Aortic Pressure Levels and Waveform Indexes in People Living With Human Immunodeficiency Virus: Impact of Calibration Method on the Differences With Respect to Non-HIV Subjects and Optimal Values - Diaz, Alejandro; Grand, Marina; Torrado, Juan; Salazar, Federico; Zócalo, Yanina; Bia, Daniel (Frontiers in Cardiovascular Medicine, 2021)
Background: There are scarce and controversial data on whether human immunodeficiency virus (HIV) infection is associated with changes in aortic pressure (aoBP) and waveform-derived indexes. Moreover, it remains unknown whether potential differences in aoBP and waveform indexes between people living with HIV (PLWHIV) and subjects without HIV (HIV-) would be affected by the calibration method of the pressure waveform. Aims: to determine: (i) whether PLWHIV present differences in aoBP and waveform-derived indexes compared to HIV- subjects; (ii) the relative impact of both HIV infection and cardiovascular risk factors (CRFs) on aoBP and waveform-derived indexes; (iii) whether the results of the first and second aims are affected by the calibration method. Methods: Three groups were included: (i) PLWHIV (n=86), (ii) HIV- subjects (general population; n=1000) and (iii) a Reference Group (healthy, non-exposed to CRFs; n=398). Haemodynamic parameters, brachial pressure (baBP; systolic: baSBP; diastolic: baDBP; mean oscillometric: baMBPosc) and aoBP and waveform-derived indexes were obtained. Brachial mean calculated (baMBPcalc=baDBP+[baSBP-baDBP]/3) pressure was quantified. Three waveform calibration schemes were used: systolic-diastolic, calculated (baMBPcalc/baDBP) and oscillometric mean (baMBPosc/baDBP). Conclusions: Regardless of CRFs and baBP, PLWHIV presented a tendency of having lower levels of aoBP and waveform-derived indexes which clearly reached statistical significance when using the baMBPosc/baDBP or baMBPcalc/baDBP calibration. HIV+ status exceeded the relative weight of other CRFs as explanatory variables, being the main explanatory variable for variations in central hemodynamics when using the baMBPosc/baDBP, followed by the baMBPcalc/baDBP calibration. The calibration approach is an important determinant to reveal differences in central hemodynamics in PLWHIV.